Антология выдающихся достижений в науке и технике. Часть 33: Электромагнитная совместимость и защита от воздействия мощных электромагнитных помех радиоэлектронного, электротехнического и электроэнергетического оборудования - Баранов, Михаил Иванович (НТУ "ХПИ", 2016)
Приведен краткий аналитический обзор основных научно-технических достижений в области электромагнитной совместимости технических средств, методов и устройств защиты радиоэлектронного, электротехнического и электроэнергетического оборудования от внешнего воздействия на него мощных импульсных электромагнитных помех, содержащих высокие напряжения, большие токи и сильные электромагнитные поля.

A brief scientific and technical review is resulted modern positions problems EMC and protection of equipment from action on them PEMI. It is shown that PEMI can result in failures in-process and death of examined equipment. Annual harm in the industrially developed countries of the world from the striking affecting of PEMI modern equipment with integral microcircuits and semiconductor devices can make ten of milliards of USD. The basic methods of protection of equipment are resulted from PEMI and protective devices (PD), intended for the increase of effectiveness of modern equipment to the action of external PEMI. Principles of work of the resulted PD and their basic technical descriptions are described.
An anthology of the distinguished achievements in science and technique. Part 33: Electromagnetic compatibility and protection from action of powerful electromagnetic interference of radioelectronic, electrical engineering and electric power equipment
Keywords: технические средства; помехозащитные устройства; обзор; ЭМС; электромагнитная обстановка; амплитудно-временные параметры; protective devices; review